2011
DOI: 10.1038/mt.2011.27
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Intracerebroventricular Replacement of Modified Human β-Hexosaminidase B for GM2 Gangliosidosis

Abstract: To develop a novel enzyme replacement therapy for neurodegenerative Tay-Sachs disease (TSD) and Sandhoff disease (SD), which are caused by deficiency of β-hexosaminidase (Hex) A, we designed a genetically engineered HEXB encoding the chimeric human β-subunit containing partial amino acid sequence of the α-subunit by structure-based homology modeling. We succeeded in producing the modified HexB by a Chinese hamster ovary (CHO) cell line stably expressing the chimeric HEXB, which can degrade artificial anionic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 34 publications
1
69
0
5
Order By: Relevance
“…We herein demonstrated that repeated administration by i.c.v.ERT using mod2B had remarkable therapeutic effects, including improvement of the motor dysfunction and life extension of SD model mice. This was caused by the incorporation of the therapeutic molecule via neural cell surface CI-M6PR, followed by delivery to lysosomes and a reduction of the accumulated substrates, as supported by our previous studies (4,5,26) in addition to the in vivo stability due to the protease resistance in the brain parenchyma. The GSEPLDS loop structure of modB may be cleaved by lysosomal endoproteases, possibly cathepsins L and B, after being incorporated and delivered to lysosomes because the proteolytic cleavage was inhibited by pretreatment of the microglial cells derived from SD mouse brain with leupeptin, a thiol protease inhibitor for cathepsins L and B (data not shown), although the enhancement of intracellular GM2 degradation by the modB replacement should be proved under the conditions in which the endoprotease activities are inhibited.…”
Section: 9mentioning
confidence: 62%
See 4 more Smart Citations
“…We herein demonstrated that repeated administration by i.c.v.ERT using mod2B had remarkable therapeutic effects, including improvement of the motor dysfunction and life extension of SD model mice. This was caused by the incorporation of the therapeutic molecule via neural cell surface CI-M6PR, followed by delivery to lysosomes and a reduction of the accumulated substrates, as supported by our previous studies (4,5,26) in addition to the in vivo stability due to the protease resistance in the brain parenchyma. The GSEPLDS loop structure of modB may be cleaved by lysosomal endoproteases, possibly cathepsins L and B, after being incorporated and delivered to lysosomes because the proteolytic cleavage was inhibited by pretreatment of the microglial cells derived from SD mouse brain with leupeptin, a thiol protease inhibitor for cathepsins L and B (data not shown), although the enhancement of intracellular GM2 degradation by the modB replacement should be proved under the conditions in which the endoprotease activities are inhibited.…”
Section: 9mentioning
confidence: 62%
“…The fibroblasts were fixed with 4% paraformaldehyde. After the samples were washed with PBS, the intracellular GM2 and Hex were detected by Ab against GM2 and human HexA (5). The specimens were viewed with the LSM700.…”
Section: Animals Sd Model Mice (Hexb -/-mentioning
confidence: 99%
See 3 more Smart Citations